2017
DOI: 10.1016/j.suronc.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

ABCB1 gene polymorphisms and response to chemotherapy in breast cancer patients: A meta-analysis

Abstract: The ABCB1 gene encodes the P-glycoprotein, an efflux pump for some antineoplastic agents which acts as a resistance mechanism to chemotherapy. Three SNPs (C3435T, C1236T and G2677T/A), are the most widely studied in ABCB1. The inconsistent conclusions about the association of these polymorphisms and the response to chemotherapy in breast cancer (BC) patients prompted us to conduct a meta-analysis. A total of nine (770 patients), five (566 patients) and three studies (367 patients) relating the ABCB1 C3435T, C1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…In the present study, however, binary logistic regression revealed that neither the genotypes of ABCB1 nor the phenotypic factors were found to influence the tumour response to docetaxel in LABC patients. Our study is reaffirming a recent meta‐analysis performed by Madrid‐Paredes et al who analysed five (n = 566) and nine (n = 770) studies of C1236T and C3435T polymorphisms, respectively. They concluded that the tumour response to chemotherapy was not influenced by these variants [C1236T—OR: 1.968, 95% CI: 0.609‐6.362 and C3435T—OR: 0.888, 95% CI: 0.558‐1.413 in the dominant model (“CT/TT” vs “CC”)].…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, however, binary logistic regression revealed that neither the genotypes of ABCB1 nor the phenotypic factors were found to influence the tumour response to docetaxel in LABC patients. Our study is reaffirming a recent meta‐analysis performed by Madrid‐Paredes et al who analysed five (n = 566) and nine (n = 770) studies of C1236T and C3435T polymorphisms, respectively. They concluded that the tumour response to chemotherapy was not influenced by these variants [C1236T—OR: 1.968, 95% CI: 0.609‐6.362 and C3435T—OR: 0.888, 95% CI: 0.558‐1.413 in the dominant model (“CT/TT” vs “CC”)].…”
Section: Discussionsupporting
confidence: 90%
“…These results are in agreement with those reported by Priyadarshini et al in the southern Indian population with BC (n = 102) [15]. In a meta-analysis study, nine of the articles included studies on the ABCB1-C3435T gene polymorphism (770 patients), where the most prevalent genotype was CT [16]; however, there were no South American studies in that analysis. Rodrigues et al studied BC patients from southeastern Brazil and found distribution patterns similar to our results with 27.9% for CC, 52.2% for CT, and 20.3% for TT [17].…”
Section: Discussionsupporting
confidence: 90%
“…The association of the ABCB1-C3435T polymorphism and response in patients with BC treated with NAC was initially suggested in a study with 68 LABC patients where those who presented better clinical responses were TT genotype carriers (OR: 4.38, 95% CI: 1.2-16.1, p = 0.029) [18]. In a metaanalysis study, nine articles involving the ABCB1-C3435T gene polymorphism (770 patients) indicated that the polymorphism was not associated with the NAC response in BC patients [16,18]. These results are similar to those in our study where we found no association between the SNP C3435T polymorphism of the MDR-1 gene and tumor response to NAC, hormone receptors, and HER-2 and Ki-67 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, better understanding of the potential pathways for blocking the MDR mechanism will help to enhance current treatments. It has already been well reported that repeated drug treatment can increase the expression of efflux pump like p-glycoprotein, allowing cancer cells to acquire a mechanism to protect themselves against anti-cancer drugs [18]. Another important mechanism is the activation of the anti-apoptotic signal to minimize DNA damage from doxorubicin, which interrupts the proliferation of the cells.…”
Section: Introductionmentioning
confidence: 99%